Explanatory models of HIV/AIDS among the Awajún population of communities intervened by the Global Fund in the framework of the strategy against HIV - Chávez, Giannina (2018)
This article presents an approach to the explanatory models on HIV/AIDS that circulate among the Awajún population of communities that have been intervened by the Global Fund stance of interrelation between the people and the within the framework of the strategy against HIV. In this sense, health is understood as an inState, and therefore, it is taken into account that medical dialogues or encounters, where this disease is discussed, are determinant in the experience of the disease, as they reflect a historical and political framework of social relations. To this end, ethnographic fieldwork was carried out during February, August and September 2017 in native communities of the Awajún ethnic group on the Cenepa River in Amazonas. Through constant and participant observation, and open and indepth interviews, we have investigated how information about HIV/AIDS circulates and is negotiated among the different actors involved in the fight against HIV, how the socio-political context affects the explanatory models and how they express their relationship with the State. The various perceptions and cases collected manifest conspiracy models about the entry of the virus into the area and models of witchcraft, questioning the existence of the disease and the potential benefit of the treatment. In that sense, they are linked to the relationship between this ethnic group, the State and the health system; as well as with conditions of poverty and inequality; that lead to the constant negotiation and reinterpretation of explanatory models within the framework of this strategy.